Comparison of prehospital triage and five-level triage system at the emergency department. Issue 11 (18th July 2017) - Tsai, Li-Heng; Huang, Chien-Hsiung; Su, Yi-Chia; Weng, Yi-Ming; Chaou, Chung-Hsien; Li, Wen-Cheng; Kuo, Chan-Wei; Ng, Chip-Jin
Abstract : Objective: There is lack of scientific evidence regarding the effectiveness of prehospital triage systems. This study compared the two-level Taiwan Prehospital Triage System (TPTS) with the five-level Taiwan Triage and Acuity Scale (TTAS) at ED arrival regarding the prediction of patient outcomes and the utilisation of medical resources. Design: This was a retrospective cohort study. Adult patients transported via the emergency medical service (EMS), who arrived at the ED of a medical centre in northern Taiwan during the study period were enrolled. TTAS acuity levels 1–2 were considered comparable to the designation of 'emergent' by the prehospital TPTS system. The outcomes were analysed by comparing TPTS and TTAS by acuity levels. Results: Among 4430 enrolled patients, 25.2% and 74.8% were classified as emergent and non-emergent by TPTS; 44.1% and 55.9% were classified as levels 1–2 and levels 3–5 by TTAS. Of the TPTS emergent patients, 15.2% were classified as TTAS levels 3–5, whereas 30.4% of TPTS non-emergent transports were classified as TTAS levels 1–2 at the ED. TTAS levels 1–2 showed better predictability than TPTS emergent level for hospitalisation rate with a sensitivity of 70.3% (95% CI 68.3% to 72.2%) versus 41.1% (95% CI 39.0% to 43.2%), and a negative predictive value of 74.8% (95% CI 73.4% to 76.0%) versus 62.6% (95% CI 61.7% to 63.5%). Conclusion: The current prehospital triage system is insufficient and inappropriate in classifying patients transported to the ED. The present study offers supporting evidence for the introduction of a five-level triage system to prehospital EMS systems.